From Father to Son: Multi-Generational Service in Legio II Adiutrix - Berecz, Gábor (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
This study investigates the patterns of multi-generational military service and the accumulation of social capital within Legio II Adiutrix, primarily based on 38 inscriptions found in Pannonia. The research identifies the father-son relationship as the most common kinship structure, though several families maintained military traditions across three generations. A significant portion of these multi-generational lineages consists of families of Oriental origin, specifically from Hemesa, Syria, for whom migration to the Danubian frontier and enlistment constituted a well-established career path. The analysis explores how military service provided substantial socio-economic advantages, including honesta missio, economic security, and social prestige. These benefits often served as a foundation for descendants to transition into civilian spheres, attaining positions in municipal administration. Despite the high risks of the profession—with epigraphic evidence recording soldiers falling in Parthian, Germanic, and Dacian campaigns—the persistent intergenerational transmission of the military career suggests that the long-term social and economic rewards outweighed the inherent dangers.